The relationship between serum 25-hydroxyvitamin D levels and dyslipidemia risk: insights from a study of elderly Chinese diabetic foot ulcer patients - Hong, Chuyi; Qi, Huiming; Gao, Xing (Frontiers in Endocrinology, 2025)
ObjectiveExisting evidence links low serum vitamin D concentrations to diabetic foot ulcer (DFU) development, but evidence on the interaction between vitamin D and blood lipids—especially in the elderly—remains limited. This study systematically evaluated the association between serum 25-hydroxyvitamin D [25(OH)D] levels and dyslipidemia in elderly DFU patients, and explored potential non-linear dose-response patterns and interaction effects.MethodsA total of 181 elderly (≥60 years) DFU patients hospitalized at the Characteristic Medical Center of Air Force Medical University in China from January 1, 2020 to May 31, 2024 were retrospectively included. Serum 25(OH)D and biochemical markers were measured using standardized laboratory protocols. (1) Differences in the detection rate of dyslipidemia were analyzed using 25(OH)D categorical variables to screen target lipid variables; (2) Multivariate logistic regression was used to assess the association between serum vitamin D and abnormal target lipid variables; (3) Restricted cubic spline (RCS) and curve fitting were employed to evaluate non-linear dose-response trends, and further piecewise regression was conducted to examine potential threshold effects; (4) Subgroup analyses were performed to investigate interactions among age, gender, duration of hyperglycemia, lifestyle, and comorbidities.ResultsThe 25(OH)D ≥50nmol/L group had a significantly lower abnormal triglyceride (TG) rate than the other two groups (p = 0.015). Logistic regression showed a dose-dependent negative correlation between 25(OH)D and abnormal TG; after covariate adjustment, each 1nmol/L increase in 25(OH)D reduced abnormal TG risk by 3.3% (adjusted OR = 0.967, 95%CI: 0.943–0.991, p = 0.009). RCS analysis confirmed an approximate linear negative correlation, with stronger protection at 25(OH)D >30.322nmol/L and no significant non-linearity. Threshold analysis identified 43.48nmol/L as the inflection point (OR = 0.907, p = 0.043 above this value), though model fitting improvement was unclear. Subgroup analyses showed significant protective effects of 25(OH)D except in season-, Wagner grade-stratified groups and those with coronary heart disease, with no significant interactions.ConclusionIn Chinese elderly DFU patients aged ≥60 years, serum vitamin D levels are dose-dependently negatively correlated with the risk of abnormal TG. However, this retrospective observational study only identifies an association, not causality, due to observational design limitations. Nevertheless, assessing elderly DFU patients’ vitamin D status may aid management, requiring verification via prospective studies or RCTs.